Blood viscosity increases the degree of coronary stenosis in coronary heart disease - Indrianto, Antonius Ferika; Samsuria, Indranila Kustarini; Kurniawan, Kusmiyati Deddy (Faculty of Medicine, Trisakti University, 2015)
BackgroundEndothelial dysfunction and associated increased blood viscosity (BV) play an important role in the formation of atherosclerosis during inflammatory processes. C-reactive protein (CRP) is a biomarker of inflammation with an active role in endothelial dysfunction and development of atherosclerosis that is marked by degree of coronary stenosis (CS). The purpose of this study was to determine the relationship of BV and CRP with varying degrees of CS among coronary heart disease (CHD) patients.MethodsThis cross-sectional study involved 24 subjects taken consecutively among patients with CHD who underwent angiography. Blood viscosity levels were determined using an Ostwald viscometer, with reference limits of 1.5 to 1.72 (cP). C-reactive protein was determined by turbidimetric immunoassay, with a normal reference value of <3 mg/L. Degree of CS was examined with angiography, where 0% = no stenosis; <50% = nonsignificant stenosis; > 50% = significant stenosis. Data was analyzed using non-parametric Spearman correlation test.ResultsThere were 17 male and 7 female subjects, with mean age of 55.96 Â± 7.29 years. The angiography results were: non-significant stenosis in 2 subjects (8.3%), significant stenosis in 22 subjects (91.7%) and none with normal stenosis. Statistical analysis of the relationship of BV with degree of CS found a moderate significant positive relationship (r=0.549; p=0.005). A poor significant positive relationship was found between CRP and degree of CS (r=0.481; p=0.017).ConclusionBlood viscosity increased the degree of CS in CHD patients. Therapy should target both BV-associated risk and angiographically evident stenosis.